Kiswahili through the Ages: The Question of Lexicon (Mwanga wa Lugha, 2018)
Kiswahili has over the past several centuries grown from a community language to an international medium of communication. This is greatly atributed to trade, politics, religion and cultural interaction and exchange.  These, among others, have over the ages been the chief rollers in Kiswahili’s expansion and development.  This means that apart from standardizing it, which was a deliberate effort, there has been no other effort to develop this vital African tongue comparable to the insurmountable effort that was expended to develop English and French, for example, even in the Swahili-speaking area of East and Central Africa. This work obviates Kiswahili’s development over several centuries, including the final decades of the last Century (i.e. the 20th Century).  It looks at its Kiswahili’s detaroriation and argues that there is need for deliberate effort to develop the language.